Modeling of dynamics of heat conductivity in the process of double-sided frying of meat on the basis of nonlinear optimization - Рамазанов, Султан Курбанович; Скрипник, В'ячеслав Олександрович; Молчанова, Наталія Юріївна (Technology audit and production reserves, 2015)
Improvement of processes of meat thermal treatment and their regularities is an important task. The purpose of the article is to present the results of research and the solution of the equation of on non-stationary heat conductivity in the process of meat double-sided frying in the condition of compression. In the article computer analytical research of dynamics of distribution of temperatures in pork meat is conducted at double-sided frying in the condition of compression, and possibilities of finding common decision for the equation of non-stationary heat conductivity are analyzed. Dynamics of temperatures change in meat is experimentally defined at double-sided frying in the condition of compression. The thermal model of double-sided frying process in the condition of compression on the basis of a nonlinear method of the generalized lowering gradient which is used for smooth nonlinear tasks is for the first time offered.